2013
DOI: 10.1038/cddis.2013.472
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of the caspase enzymes in satellite cells from aged and young subjects

Abstract: Satellite cell (SC) proliferation and differentiation have critical roles in skeletal muscle recovery after injury and adaptation in response to hypertrophic stimuli. Normal ageing hinders SC proliferation and differentiation, and is associated with increased expression of a number of pro-apoptotic factors in skeletal muscle. In light of previous studies that have demonstrated age-related altered expression of genes involved in SC antioxidant and repair activity, this investigation was aimed at evaluating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 41 publications
7
37
0
Order By: Relevance
“…Mechanistically, the factors responsible for the loss of SC with inactivity are not defined but may be related to cell apoptosis. For example, SC isolated from aged muscle display greater rates of apoptosis concomitant with rises in caspase family members and cell death genes . In contrast, resistance exercise can induce an expansion of the SC pool in older skeletal muscle despite a delayed type II fibre‐associated SC response .…”
Section: Discussionmentioning
confidence: 66%
“…Mechanistically, the factors responsible for the loss of SC with inactivity are not defined but may be related to cell apoptosis. For example, SC isolated from aged muscle display greater rates of apoptosis concomitant with rises in caspase family members and cell death genes . In contrast, resistance exercise can induce an expansion of the SC pool in older skeletal muscle despite a delayed type II fibre‐associated SC response .…”
Section: Discussionmentioning
confidence: 66%
“…A similar apoptotic tendency is also seen in adult stem cells. Satellite cells, which are myogenic stem cells important for skeletal muscle regeneration, from old subjects (mean age = 71 years) are more prone to apoptotic cell death, compared with those from young subjects (mean age = 27 years) [60]. The cell death genes upregulated in the satellite cells from old subjects include the caspase 9 gene, whose activation is promoted by cytochrome c [61].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of ROS are associated with metabolic diseases like diabetes [16,20,36], which may contribute to the loss of myoblast function, increase myoblast cell death [33] and further exacerbate muscle repair in aging. Fulle and colleagues [25] have demonstrated that a high percentage of the myogenic precursor cells from elderly muscles undergo apoptosis triggered by mitochondrial-associated caspase-9 and this appears to be closely linked to the high ROS levels that are found in aged muscles [20]. Thus, we predict that strategies to attenuate high ROS levels should reduce apoptosis in myoblasts and improve muscle differentiation/repair in aging and in other diseases that have elevated ROS levels.…”
Section: Introductionmentioning
confidence: 86%